Book Review: Anna Backman Rogers, Still Life: Notes on Barbara Loden's Wanda (Santa Barbara CA: Punctum Press, 2021). Issue 1 (14th July 2022) - Pember, Alice
Abstract : Abstract: Anna Backman Rogers, Still Life:Notes on Barbara Loden's Wanda (Santa Barbara CA: Punctum Press, 2021), pp. 19–149, ISBN 978-1-953035-68-4 (pb), 20; ISBN978-1-953035-69-1 (eb PDF), free.